Fluorescence in situ hybridisation (FISH) analysis of chromosomal aberrations in gastric tissue: The involvement of "Helicobacter pylori". - Lisa Williams (2004)
Gastric cancer is a common cause of cancer death in the UK. It most often presents in patients when the disease is advanced, and hence treatment options are limited. As such, studies on the pre-malignant stages of gastric cancer, and interest in the mechanisms of the carcinogenic process (reactive oxygen species, ROS) and the agents that may drive the carcinogenic pathway {Helicobacter pylori infection), are important, with a view to improving disease outcome. This series of experiments has firstly shown, using CBMN assay +/- kinetochore staining and interphase FISH, that ROS causes aneuploidy of chromosomes 4, 8, 20 and 17(p53) in a human cell line. Secondly, gastric cells have been collected using endoscopic cytology brush techniques, and prepared, such that interphase FISH could be performed. Again, aneuploidy of chromosomes 4, 8, 20 and 17(p53) were detected in normal gastric mucosa, gastritis and intestinal metaplasia. The level of aneuploidy detected increased as disease severity increased. Amplification of chromosome 4, amplification of chromosome 20 and deletion of chromosome 17(p53) were the more significant findings. The degree of chromosomal abnormalities detected increased further, in a stepwise manner, when gastric dysplasia and gastric adenocarinoma cells were studied. Hence, a role for these abnormalities may exist in the initiation of, and the progression to, gastric cancer. The presence of H. pylori was also determined in the gastric tissue studied using histological analysis and PCR technology. Detection rates were comparable. The more virulent strain of H. pylori, Cag A, was found to be associated with increased disease pathology and chromosomal abnormalities, yet numbers were small. The amplification of chromosome 4 in gastric tissue was again highlighted in association with H pylori infection, hence it may reflect a role for chromosome 4 in the initiation of gastric cancer.